Given that a , b and c are real numbers such that a + b + c = 0 , compute b 2 + c 2 − a 2 1 + c 2 + a 2 − b 2 1 + a 2 + b 2 − c 2 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a+b+c=0 therefore a, b and c=0 so 1/0+1/0+1/0=0
G i v e n a + b + c = 0 . ⇒ a = − ( b + c ) . ⇒ a 2 = b 2 + c 2 + 2 b c . . . ( 1 ) N o w , b 2 + c 2 − a 2 = b 2 + c 2 − ( b 2 + c 2 + 2 b c ) . . . . [ S u b s t i t u t i n g t h e v a l u e o f a f r o m ( 1 ) ⇒ b 2 + c 2 − a 2 = − 2 b c . S i m i l a r y f o r t h e o t h e r t w o e x p r e s s i o n s . [ ( c 2 + a 2 − b 2 ) & ( a 2 + b 2 − c 2 ) ] . N o w , b 2 + c 2 − a 2 1 + c 2 + a 2 − b 2 1 + a 2 + b 2 − c 2 1 = − ( 2 b c 1 2 a c 1 2 a b 1 ) . ⇒ − ( 2 a b c a + 2 a b c b + 2 a b c c ) = 0 .
Log in to reply
Excellent. Why don't you post this as a solution here?
Exactly the same way Bro.
1/0=infinite....not zero
a+b+c=0 therefore a,b and c=0 so 1/0+1/0+1/0=0
Log in to reply
No its wrong because 1/0 is not defined. And also a, b, c are not necessarily =0. Only their sum is 0.
Log in to reply
Exactly a+b+c=0 always doesnt mean a,b & c are also 0. They may be negative integers
mitali ur answer is write but steps are wrong any number by 0 is undefined
add the fractions. it will leave you with an a+b+c numerator which means 0. therefore the fraction is 0.
a+b+c=0 = 0+0+0=0 0square is 0 (1/0)+(1/0)+(1/0)=0
is this right sai venkatesh?
a+b+c=0...therefore...(a+b)^2 =c^2....=> a^2+b^2=c^2 -2ab.........therefore manipulating it you get it as zero...
Problem Loading...
Note Loading...
Set Loading...
It is given that a + b + c = 0 ⇒ a = − ( b + c ) , b = − ( c + a ) , c = − ( a + b ) .
Now consider b 2 + c 2 − a 2 = b 2 + c 2 − [ − ( b + c ) ] 2 = b 2 + c 2 − ( b 2 + 2 b c + c 2 ) = − b c .
Therefore,
b 2 + c 2 − a 2 1 + c 2 + a 2 − b 2 1 + a 2 + b 2 − c 2 1 = − 2 b c 1 − 2 c a 1 − 2 a b 1
= − 2 1 ( b c 1 + c a 1 + a b 1 ) = − 2 1 ( a b c a + b + c ) = − 2 1 ( a b c 0 ) = 0